2002
DOI: 10.1093/emboj/cdf404
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin and lipid binding to synaptobrevin regulates calcium-dependent exocytosis

Abstract: Neurotransmitter release involves the assembly of a heterotrimeric SNARE complex composed of the vesicle protein synaptobrevin (VAMP 2) and two plasma membrane partners, syntaxin 1 and SNAP-25. Calcium in¯ux is thought to control this process via Ca 2+ -binding proteins that associate with components of the SNARE complex. Ca 2+ /calmodulin or phospholipids bind in a mutually exclusive fashion to a C-terminal domain of VAMP (VAMP 77±90 ), and residues involved were identi®ed by plasmon resonance spectroscopy. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
120
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 45 publications
10
120
0
1
Order By: Relevance
“…Release of hGH from toxin-treated, permeabilized PC12 cells transfected with botulinum neurotoxin type B (botB)-resistant syb2 (Q76V,F77W) was measured essentially as described previously (Quetglas et al, 2002) in the presence of recombinantly expressed endopeptidase light chain (LC) of botB (botB/ LC). BotB/LC was purified as described previously (Sutton et al, 2005), was of high homogeneity as assessed by SDS-PAGE, and it showed endopeptidase activity comparable with native botulinum neurotoxin by using an in vitro vesicle-associated membrane protein peptide cleavage assay (Sutton et al, 2005).…”
Section: Toxin Rescue Assaysmentioning
confidence: 99%
“…Release of hGH from toxin-treated, permeabilized PC12 cells transfected with botulinum neurotoxin type B (botB)-resistant syb2 (Q76V,F77W) was measured essentially as described previously (Quetglas et al, 2002) in the presence of recombinantly expressed endopeptidase light chain (LC) of botB (botB/ LC). BotB/LC was purified as described previously (Sutton et al, 2005), was of high homogeneity as assessed by SDS-PAGE, and it showed endopeptidase activity comparable with native botulinum neurotoxin by using an in vitro vesicle-associated membrane protein peptide cleavage assay (Sutton et al, 2005).…”
Section: Toxin Rescue Assaysmentioning
confidence: 99%
“…Amperometric measurement of exocytotic catecholamine release was performed as described previously (Ohyama et al, 2002;Quetglas et al, 2002) except that the chromaffin cells were stimulated with 60 mM KCl. Microinjection was performed using a 6-d-old culture of chromaffin cells on collagencoated coverslips.…”
Section: Amperometrymentioning
confidence: 99%
“…For these reasons, we used chromaffin cell exocytosis to investigate the function of the Ca 2ϩ -dependent interaction between syntaxin-1A and myosin-Va. Amperometric measurements were used to examine the physiological role of myosin-Va-syntaxin-1A binding because it is a powerful method not only for quantitative measurement of exocytosis but also for characterizing the mechanism of exocytosis (Segre et al, 2000;Fisher et al, 2001). We therefore performed an amperometric assay of catecholamine release for dense-core vesicles in chromaffin cells (Ohyama et al, 2002;Quetglas et al, 2002), which are known to possess myosin-Va (Rosé et al, 2003). We found that the syntaxin-1A specifically reduced the exocytotic frequency, whereas syntaxin-1A [191-240 L222E] fragment had no effect (Figure 4, A and B).…”
Section: Interference With Syntaxin-1a-myosin-va Complex Formation Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Several proteins have been invoked in regulating synaptobrevin. For instance, calmodulin was reported to bind to the C-terminal region of synaptobrevin (residues 77-90) in a calcium-dependent manner (Quetglas et al, 2002). Calmodulin was shown to compete with membrane binding of this region, and it was proposed that calmodulin binding inhibits rather than activates synaptobrevin (de Haro et al, 2004).…”
mentioning
confidence: 99%